Proceedings of the Tenth International Workshop on Variability Modelling of Software-Intensive Systems 2016
DOI: 10.1145/2866614.2866627
|View full text |Cite
|
Sign up to set email alerts
|

Search-based Similarity-driven Behavioural SPL Testing

Abstract: International audienceDissimilar test cases have been proven to be effective to reveal faults in software systems. In the Software Product Line (SPL) context, this criterion has been applied successfully to mimic combinatorial interaction testing in an efficient and scalable manner by selecting and prioritising most dissimilar configurations of feature models using evolutionary algorithms. In this paper, we extend dissimilarity to behavioural SPL models (FTS) in a search-based approach, and evaluate its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…From the inferred models, we extract a set of dissimilar (based on the Jaccard distance ) abstract object behaviours (➃ in Figure ). For abstract object behaviour extraction, we use the VIBeS model‐based testing tool.…”
Section: Methodsmentioning
confidence: 97%
“…From the inferred models, we extract a set of dissimilar (based on the Jaccard distance ) abstract object behaviours (➃ in Figure ). For abstract object behaviour extraction, we use the VIBeS model‐based testing tool.…”
Section: Methodsmentioning
confidence: 97%
“…Another (complementary) approach that has been used is to separately consider test selection and prioritisation (see, for example, [1,19,29,31,47,48,55,58,61]). These approaches can decrease the difficulty of the considered problem from many objectives to multiple objectives.…”
Section: Optimisation Approachmentioning
confidence: 99%
“…Thus, the problem is to find a test suite (sequence of valid products) that is likely to be a good solution (in terms of selection and prioritisation). It has been observed that a number of properties of good test suites can be captured by objective functions that map a test suite to a value that represents how 'good' this test suite is according to the properties (see, for example [19,23,29,31,32,48,51,58,61,71,72,74]). For example, a fault might be associated with the interaction of a pair of features and so we might want to test as many such interactions as possible (pairwise coverage).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations